Heat Shock Stimulate Division of Hypocotyle Suspension Culture of Dianthus caryophyllus L. - Sahla Mohamed Zeadan (College of Education for Pure Sciences, 2018)
The study succeeded in establishing a fine cell suspension derived from callus of carnation, Dianthus caryophyllus L. Hypocotyle explants in liquid MS medium supplemented with 0.5 mgL-1 2,4-D and 0.1 mgL-1 BA. The cells begin its first division within 24 h. These cell were continued their subsequent divisions to produce 142x103 cell/ml culture after five days of initiation. Results indicated that exposure of cell suspension to 20, 25, 30, 35, 40, 45, and 50oC short-term 5, 10 min. and long-term 15-20 min. stimulate the division of cells suspension in all treatments. Heat shock sustained the division of cell cultured in multiple drop array (MDA) technique and increase the formation of cellular colonies which produced a numerous of calli primordia. The total number of colonies was 959 developed when cells exposed to with the short-term 35oC/5 min heat shock. The produced calli was green in colour and friable in texture.